CAT (T) is Out of the Bag - Siddiqui, Rehman (Pakistan Journal of Ophthalmology, 2011)
The much anticipated results of Comparison of AMD Treatment Trial (CATT) were out a few weeks ago. CATT study is a landmark trial in comparative clinical research. Indeed, the study was not sponsored by the pharmaceutical industry instead it was supported by National Eye Institute (NEI), USA. Dr Martin and his colleagues are to be applauded for undertaking such a high quality study. For this study to take place various laws governing use of medications and reimbursement in the USA had to be amended. The study was published in New England Journal of Medicine1 and an editorial by Dr. Philip Rosenfeld (the